Green banking disclosure: A bibliometric analysis - Sa Nguyen Tran; Dao Thi Thieu Ha (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This study uses a bibliometric approach to analyze the influence and productivity of research on green banking disclosure from 1993 to 2023. We utilize the Web of Science Core Collection database to gather the 112 articles, and Biblioshiny software to analyze and visualize bibliometric data to evaluate literature. Through utilizing co-citation, co-authorship, keyword co-occurrence, and science mapping, the results of the study show that the amount of papers published in the field of green banking disclosure has increased dramatically over the past seven years, as have the contributions of many authors, institutions from various countries, and collaboration between researchers from different institutions. The analysis results of the other criteria show that institutional theory, asymmetry information theory, and content analysis were used to study green banking disclosure, which is related to corporate social responsibility and sustainability. This thorough synthesis and analysis of green banking disclosure will add to the body of knowledge in this field by enhancing understanding of the subject and pointing out areas of research deficiency that require attention.